Unsaturated hydro-mechanical-chemical constitutive coupled model based on mixture coupling theory: Hydration swelling and chemical osmosis - Chen, X. (Elsevier Ltd, 2016)
Very low permeability soils and rocks may act as actual semi-permeable membranes and also have the potential to swell if they contain smectite clay minerals. This study extends mixture coupling theory for unsaturated, very low permeability swelling rock, based on non-equilibrium dynamics and Biot's elasticity, and develops new advanced coupled mathematical formulations, by including unsaturated chemical osmosis and hydration swelling. Helmholtz free energy has been used to derive the link between solid deformation and multiphase transport. Darcy's law has been extended and the influence of swelling on stress and strain has been included. The mathematical formulation shows that swelling capacity may have a strong influence on the deformation of host rocks (e.g. for nuclear waste disposal) in the chemical osmosis process, which is demonstrated by a numerical simulation of two representative cases. Important engineering applications of this model and analysis are highlighted. Â© 2016 Elsevier Ltd. All rights reserved.